PELATIHAN PEMBUATAN SHAMPO DI RPTRA KELURAHAN MERUYA SELATAN - Yuliarty, Popy; Anggraini, Rini (Universitas Mercu Buana, 2023)
The rapid development of social media has a positive impact on human life, one of which is encouraging business opportunities in all fields such as making it easy to achieve product marketing. This development provides an opportunity for anyone to do business and market it through social media, this is what prompted the service team to provide training on making shampoo through a home business that can be done by all levels of society. Hair is a crown for humans, especially for women. Shiny, clean, fragrant and healthy hair is every woman's dream. Shampoo is a product that can help make this happen. Given the easy process of making this shampoo, knowledge about making this shampoo needs to be disseminated, because apart from making people smarter, it can also motivate people to become entrepreneurs, especially since shampoo is a primary need that is evenly distributed in all levels of society. Shampoo-making training is expected to broaden the horizons of mothers and young women and can be a provision for them to do entrepreneurship, which if pursued will be able to help the family's finances. This training has been carried out well at RPTRA Menara and received positive responses from the participants.